ENERGY BALANCE AND EFFICIENCY IN WOOD SAWDUST BRIQUETTES PRODUCTION - Vale, Ailton Teixeira; Gentil, Luiz Vicente (Floresta, 2014)
Abstract Energy balance and efficiency for densified sawdust production. The industrial wood briquette making process is an alternative to add value to forestry waste and involves the compaction of sawdust at high pressure and temperature. The present study was performed in an industry in the state of Goiás, Brazil. All kinds of energy involved in the wood briquette manufacturing process were qualified and quantified, in all stages of the process. The methodology used was based on Cotrim (1992), Silva (2001), (BEN, 2007), Inconprera (2008) and NBR 8633. The total energy demand to produce one ton of Pinus wood briquettes using sawdust at 43.8% moisture was 435 kWh. When producing the same amount of briquettes at 11% humidity, this value fell to 101.66 kWh per ton. Thus, drying process of sawdust consumes 76.63% of all the energy used for manufacturing. The amount of energy required for the production of 1 ton of briquettes corresponds to 10.8% (wet sawdust) and 4.37% (dry sawdust) of the energy contained in this one ton of briquettes. Keywords: Wood densification; industry of briquette; energy. Resumo Eficiência e balanço energético na fabricação de briquetes de madeira. A briquetagem é uma alternativa para agregar valor a resíduos de origem agro florestal e consiste na compactação da serragem a elevadas pressões e temperatura. Este trabalho foi desenvolvido em uma indústria no estado de Goiás, onde foram quantificadas e caracterizadas todas as energias envolvidas no processo de fabricação de briquete em todas as etapas do processo industrial. A metodologia utilizada baseou-se em Cotrim (2003), Silva (2001), Brasil (2007), Inconprera (2008), ABNT (1984). A unidade utilizada foi kWh/t de briquete fabricado. A demanda total de energia para fabricar uma tonelada de briquete a partir de serragem de Pinus com 43,8% de umidade foi de 435 kWh/t. Quando se fabrica a mesma a quantidade de briquetes agora com umidade de 11%, este valor cai para 101,66 kWh/t. Assim, a secagem da serragem consome 76,63% de toda energia de fabricação. Entretanto com a serragem a 11% de umidade a maior demanda de energia eletricidade, com 64,06%. A energia necessária para produzir uma tonelada de briquete com serragem úmida (43,8%) corresponde a 10,8% da energia contida nesta 1 tonelada de briquete e com serragem seca a 4,37%. Palavras-chave: Briquetagem de madeira; indústria de briquete; energia.